On the solution of NP-hard linear complementarity problem - Joaquim J. Júdice (2002)
In this paper two enumerative algorithms for the Linear Complementarity Problems (LCP) are discussed. These procedures exploit the equivalence of the LCP into a nonconvex quadratic and a bilinear programs. It is shown that these algorithms are efficient for processing NP-hard LCPs associated with reformulations of the Knapsack problem and should be recommended to solve difficult LCPs.